THE FORMATION OF INDIAN MATHEMATICS - Musobek Fayzullayev (Journals Park Publishing, 2022)
The article tells about the history of the formation of mathematics fabibibg and numbers in the state of ancient India. In the early days of the theme of Mecca, historical sources of the ancient Indian state of kadimgi were used.
Keywords: mathematics; numbers; education